Association of rs6983267 at 8q24, HULC rs7763881 polymorphisms and serum lncRNAs CCAT2 and HULC with colorectal cancer in Egyptian patients. Issue 1 (December 2017) - Shaker, Olfat; Senousy, Mahmoud; Elbaz, Eman
Abstract The impact of HULC rs7763881 on colorectal cancer (CRC) susceptibility is not yet known. Also, the biological function of the cancer-related rs6983267 remains unclear. We investigated the association of these SNPs with the risk of CRC and adenomatous polyps (AP), their correlation with CCAT2 and HULC expression, and the potential of serum CCAT2 and HULC as biomarkers for CRC. 120 CRC patients, 30 AP patients, and 96 healthy controls were included. Genotyping and serum lncRNAs were assayed by qPCR. Studied SNPs were not associated with AP susceptibility. rs6983267 GG was associated with increased CRC risk, whereas rs7763881 AC was protective. rs7763881 and rs6983267 CT haplotype was protective. Serum CCAT2 and HULC were upregulated in CRC and AP patients versus controls and discriminated these groups by ROC analysis. rs6983267 GG and rs7763881 AA patients demonstrated higher serum CCAT2 and HULC compared with GT/TT and AC, respectively. rs6983267 and serum HULC predicted CRC diagnosis among non-CRC groups (AP + controls) by multivariate analysis. Studied SNPs or serum long noncoding RNAs weren't correlated with nodal or distant metastasis. In conclusion, rs6983267 and rs7763881 are potential genetic markers of CRC predisposition and correlate with serum CCAT2 and HULC, two novel potential non-invasive diagnostic biomarkers for CRC.